Influence of choroidal thickness on subfoveal choroidal thickness measurement repeatability using enhanced depth imaging optical coherence tomography - Cho, A R; Choi, Y J; Kim, Y T (Eye (London), 2014)
Purpose To determine the influence of choroidal thickness (CT) and image setting on repeatability of subfoveal choroidal thickness (SFCT) manual measurement using enhanced depth imaging optical coherence tomography (EDI-OCT). Methods This retrospective study included 189 eyes from 189 adults. Two observers (A and B) measured the SFCT from 1 : 1 micron and 1 : 1 pixel images for evaluation of interobserver repeatability. Observer A performed a single additional measurement for intraobserver repeatability. Results The mean age was 45.1±11.1 years. The mean SFCT from 1 : 1 pixel and 1 : 1 micron images were 315.3±89.2 and 312.6±88.4 μ m, respectively. The subjects were divided into three subgroups based on the mean CT from 1 : 1 pixel images: 26 eyes belonged to thin CT group, 111 eyes to intermediate CT group, and 52 eyes to thick CT group. Interclass coefficients (ICCs) exhibited high intraobserver repeatability. Interobserver ICCs were also high, except for thick CT group with 1 : 1 pixel image (ICC≤0.75). Intraobserver correlation coefficients were high regardless of CT. Interobserver correlation coefficients for 1 : 1 pixel images were 0.896 in thin CT group, 0.680 in intermediate CT group, and 0.624 in thick CT group, respectively ( P <0.0001). The interobserver ICCs and correlation coefficients from 1 : 1 micron images were slightly higher than from 1 : 1 pixel images. Conclusions The repeatability for the two observers was reduced in thick CT group despite high total repeatability. 1 : 1 Micron images provided slightly better repeatability in interobserver measurements. CT measurements should be interpreted cautiously, particularly for a thick choroid.